Minimalisir Waste dalam Upaya Pengurangan Waktu Proses Produksi PT X - Bobby Setiawan; I Gede Agus Widyadana (Jurnal Titra, 2019)
PT X produce heat exchanger where one of their line production is CU Condensor line which produce condensor. Problem faced is, production process takes longer than estimate cycle time. Suspected wastes that cause production process run slower. Therefore, Waste Assesment Model (WAM) is built to know what critical waste is and find that waste defect that need more attention to solve. Further, it is strived to reduce waste defect by using Root Cause Analysis to reduce waste defect. Analysis result show that the biggest defect is painting problem, and 81.3% of them are sagging, peel off, and unpainted part. Three kind of defective are searched for root cause use cause & effect diagram. Each root cause are solved with solution in hope to reduce defect until 36.74%. The reduction of defect percentage can reduce repair time and indirectly reduce the production process time of the condenser unit.